Ejercicio sobre las opiniones y expectativas de los estudiantes de Derecho : entre la conformidad y la crítica - Pezzetta, Silvina (2014)
As a Law Professor at the University of Rosario Law School I proposed to my students an activity for me to get to know their thoughts about the education they were receiving. The activity was simple and informal, they have to answer two questions. The first one was: What were your expectations when you first arrived to the Law School? The second one was: What are the deficiencies that you find, if any, in your education? The questions were read aloud and the students answered them in their own sheets of papers. The informality was a deliberate decision to gain some flexibility that would allow some creativity and freedom in their answers. In this paper I present the results of the exercise but first I will provide a theoretical framework and some other results about \nArgentinean legal education.